Muir Stephen Fairchild papers - Fairchild, Muir Stephen, 1894-1950.
Correspondence, reports, speeches, and articles relating to Fairchild's service as U.S. Air Force vice chief of staff. Includes printed matter prepared by Fairchild for the Air Corps Tactical School. Correspondents include Laurence Sherman Kuter, Curtis E. LeMay, Elwood R. Quesada, and Hoyt S. Vandenberg.
U.S. Army and Air Force officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Kuter, Laurence Sherman, -- 1905- -- Correspondence; LeMay, Curtis E. -- Correspondence; Quesada, Elwood R. -- 1904- -- Correspondence; Vandenberg, Hoyt Sanford, -- 1899-1954 -- Correspondence; United States. -- Air Force; United States. -- Army. -- Air Corps; United States. -- Army. -- Air Corps Tactical School; Air Force officers; Army officers